গনমাধ্যম ও সমাজ - মঞ্জু, কামরুল হাসান; স্নিগ্ধা, জান্নাতুল ফেরদৌস (এম. এম. সি. সেমিনার সংকলন ;)
Contributed articles on social perspectives of mass media and adequacy of press coverage in Bangladesh; edited papers of various seminars.